Identity Politics, Core State Powers and Regional Integration: Europe and beyond - Tanja A. Börzel; Thomas Risse (JCMS: Journal of Common Market Studies, 2020)
This article concentrates on the path from the development of collective identities to the integration of core state powers. Firstly, we focus on the European experience. We argue that the identities of political, economic, and social elites have been crucial for the evolution of European integration. With regard to mass public opinion, European integration has been made possible by a consensus of EU citizens with inclusive national identities. Most recently, the politicization of EU affairs in many member states has been driven by populist forces mobilizing minorities with exclusive nationalist identities. Secondly, we discuss the extent to which insights from Europe have travelled to other regions of the world. Elites involved in region-building almost always develop identity narratives linking their national experience to the respective regions. Moreover, there is evidence that the difference between inclusive and exclusive nationalist identifications has also travelled beyond Europe.
Keywords: 330; comparative regionalism; European integration; European identity; identity politics